Translation, hospitality and conflict: Language mediators as an activist community of practice across the Mediterranean - Taronna, Annarita (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This article reports on a research project that involved conducting interviews with a group of language mediators who assisted the newlyarrived migrants in Southern Italy by not only interpreting for them, but also advising and helping the “boat people” to claim and negotiate their rights in the hosting country. Interview questions addressed a range of urgent issues, many of which demonstrate how the practice of language mediation is particularly relevant in today’s context of migration emergency. Indeed, it profoundly shapes how we think about terms such as language, negotiation, contact, conflict, hospitality and community, and how we consider the roles of the mediators in building effective cross-border solidarity networks in real time. However, the interview answers do not provide an idealistic and idealized vision of welcoming the other. Rather, they outline a geography of proximity marked by the ancient hospes–hostis dichotomy that connotes the complexity, the ambiguity, the uncertainty, the unpredictability and the contingency characteristic of relations with the other.